Combined rTMS to the auditory cortex and prefrontal cortex for tinnitus control in patients with depression: a pilot study. (June 2013) - Park, Sera; Park, Hae-Jung; Kyeong, Sung-Hyon; Moon, In Seok; Kim, Minbum; Kim, Hee Nam; Choi, Jae-Young
Abstract Conclusion: The study showed that combined repetitive transcranial magnetic stimulation (rTMS) on the auditory cortex and prefrontal cortex has more benefit than rTMS on the auditory cortex alone for tinnitus control in patients with depression. Further studies for the most optimal combination of stimulation on both areas are needed. Objective: Recent studies suggest that the neuronal network changes of chronic tinnitus are beyond the auditory pathway. There is increasing evidences for the application of rTMS on multiple brain cortices in addition to the auditory cortex for the treatment of tinnitus. Sequential rTMS was performed on the auditory cortex alone as well as the auditory cortex combined with prefrontal cortex in patients with both chronic tinnitus and depression. Methods: Patients who presented with chronic tinnitus of more than 1 year were enrolled in the present study (seven males, four females; mean age 54 years). To select the site for the rTMS, PET CT was performed. Patients received the first rTMS on the primary auditory cortex for 5 days and on the primary auditory cortex and prefrontal cortex in the second application after tinnitus relapse. The Tinnitus Handicap Inventory (THI), visual analog scale (VAS), and Beck Depression Inventory (BDI) were evaluated before and after rTMS. Results: The mean THI score of the eight patients with depression changed from 77.5 ± 15 to 61.8 ± 20.1 after the second rTMS. There was statistical significance only for the second rTMS. The VAS score changed from 8.6 ± 1.6 to 6.3 ± 1.8 after the first rTMS and from 7.6 ± 2.4 to 4.6 ± 2.7 after the second rTMS, showing statistically significant changes both times. The THI changes after the second rTMS were greater than after the first rTMS, and the changes in VAS score showed a similar pattern. The changes in BDI score, which indicates the severity of depression, showed a variable pattern after rTMS. Patients with mild depression (10≤ BDI score <16, n = 4) showed significant improvement of THI with the second combined rTMS (ΔTHI = 24.5) as compared with the first rTMS on the auditory area (ΔTHI = 6). In contrast, combined rTMS did not show any better improvement on THI (ΔTHI = 6.5) than the first rTMS on the auditory cortex (ΔTHI = 7) in patients without depression (BDI <10, n = 3) and patients with moderate to severe depression (BDI ≥16, n = 4).